2006
DOI: 10.1177/0165025406066757
|View full text |Cite
|
Sign up to set email alerts
|

Childhood aggression, depressive symptoms, and peer rejection: The mediational model revisited

Abstract: The goals of the current study were to investigate whether peer rejection mediated the relation between aggression and depressive symptoms in childhood, and if so, whether this mediational pathway was specific to the reactive subtype of aggression. Participants were 57 second-grade children (22 girls and 35 boys). Data on reactive aggression, proactive aggression, depressive symptoms, and peer rejection were collected from four sources (parents, teachers, peers, and self ). Results revealed that reactive aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 51 publications
4
25
0
4
Order By: Relevance
“…These data clearly show that adverse parenting behaviors, particularly frequent corporal punishment, are important contributors to the growth of peer aggression in young children. High levels of aggressive behavior in kindergarten have been linked with chronic, cascading social and academic difficulties that include peer victimization (e.g., Morrow, Hubbard, McAuliffe, Rubin, & Dearing, 2006), use of illicit substances (Dodge et al, 2009), and poor educational attainment in early adulthood (Vitaro, Brendgen, Larose, & Tremblay, 2005). Thus, our data highlight the need for family intervention during the early preschool years.…”
Section: Resultsmentioning
confidence: 99%
“…These data clearly show that adverse parenting behaviors, particularly frequent corporal punishment, are important contributors to the growth of peer aggression in young children. High levels of aggressive behavior in kindergarten have been linked with chronic, cascading social and academic difficulties that include peer victimization (e.g., Morrow, Hubbard, McAuliffe, Rubin, & Dearing, 2006), use of illicit substances (Dodge et al, 2009), and poor educational attainment in early adulthood (Vitaro, Brendgen, Larose, & Tremblay, 2005). Thus, our data highlight the need for family intervention during the early preschool years.…”
Section: Resultsmentioning
confidence: 99%
“…When compared with parental support and teacher support, student–student support was the strongest correlate of adolescents’ depressive symptoms for girls and boys and for Chinese and American adolescents. Research has consistently suggested that peer rejection is a particular strong correlate of depressive symptoms during adolescence (Morrow, Hubbard, McAuliffe, Rubin, & Dearing, 2006; Pedersen, Vitaro, Barker, & Borge, 2007; Prinstein & Aikins, 2004). The striking aspect of this finding is the lack of nationality or sex differences in the association between peer support and depressive symptoms, drawing attention to the importance of peer support (or the negative influence of peer rejection) in both the American and Chinese contexts and for both boys and girls.…”
Section: Discussionmentioning
confidence: 99%
“…However, some children show persisting externalizing problems and do not reduce their aggressive behaviors across the transition from the preschool period to the middle- and late-childhood period (NICHD Early Child Care Research Network, 2004). These children have been shown to have a wide range of adjustment problems in both social and academic domains across the school-age years (Caspi & Moffitt, 1995; Dodge, Greenberg, & Malone, 2008; Morrow, Hubbard, McAuliffe, Rubin, & Dearing, 2006). Thus, research has focused on identifying specific developmental and child-level characteristics that predict persisting forms of aggressive and externalizing behavior problems into the early school period (Shaw, Gilliom, Ingoldsby, & Nagin, 2003) in order to more effectively target children at highest risk of poor outcomes via intervention or treatment (i.e., those who are less likely to desist from normatively high initial levels of aggression).…”
mentioning
confidence: 99%